Analysis of Complete Systematic Land Certification (PTSL) to Increase the Economic Value of Community Land - Muhammad Yamin Lubis; Ivana Novrinda Rambe; Erna Herlinda; Nurhadi Ahmad Juang; Nurhimmi Falahiyati (Mahadi: Indonesia Journal of Law, 2026)
This research is motivated by the persistently high number of unregistered land parcels and the low level of legal certainty regarding community land ownership, which has resulted in limited access to economic opportunities and capital. The Complete Systematic Land Registration Program (PTSL) implemented by the government aims to accelerate asset legalization through the mass issuance of land title certificates. However, the effectiveness of PTSL in increasing the economic value of community land still requires empirical and juridical examination. This study aims to analyze the implementation of PTSL, identify the obstacles encountered, and assess the impact of land certification on enhancing the economic value of community land. The research method employed is normative legal research with a socio-juridical approach. Secondary data were obtained from statutory regulations, academic literature, and policy documents related to PTSL and land law. The analysis was conducted qualitatively to evaluate the relationship between legal certainty of land rights and the increase in economic value. The findings indicate that PTSL provides legal certainty and protection of land rights, increases land market value, and expands community access to financial institutions through credit schemes using land certificates as collateral. Certification also enhances investor confidence and strengthens the bargaining position of landowners. Nevertheless, administrative constraints, limited public understanding, and the suboptimal utilization of certificates as instruments of economic empowerment remain challenges. Therefore, PTSL significantly contributes to increasing the economic value of land, although strengthening community assistance and legal literacy is still necessary.